The concept of man in Kirkhart's consociated model a phenomenological existential approach - De los Santos-Guina, Carolina T. (Philippine Journal of Public Administration, 1979)
The distinctive mark of phenomenology as methodology lies in its capacity to reveal essences. Applied to the Weberian and consociated models, phenomenology becomes a useful tool in scrutinizing organizational experiences (reality) against ideal types (thoughts about reality). The choice of man as the focus of analysis underscores the need to arrive at an understanding of the individual as he responds to and is affected by organizational stimuli and the environment at large. This is more so because the consociated model is essentially based on participative theory and has strong existentialist underpinnings -implying that man has full capacity to be aware of his existence, consequently to be responsible for it, and to attain self-fulfillment through close interpersonal relations, creativity and spontaneity. It is within this framework that the dehumanizing tendencies of bureaucratic forms are best understood and the search for more relevant organizational forms becomes more meaningful.